2017
DOI: 10.1002/ejp.1112
|View full text |Cite
|
Sign up to set email alerts
|

Skin denervation does not alter cortical potentials to surface concentric electrode stimulation: A comparison with laser evoked potentials and contact heat evoked potentials

Abstract: Capsaicin-induced epidermal denervation abolishes laser evoked potentials (LEPs) and contact heat evoked potentials (CHEPs), but leaves unaffected pain-related evoked potentials by surface concentric electrode (SE-PREPs). These findings suggest that unlike LEPs and CHEPs, SE-PREPs are not selectively mediated by nociceptive system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…As predicted based on LEP studies in humans 35,36 , peripheral application of capsaicin (causing defunctionalisation of C-fibres 30 ) resulted in a large reduction in the amplitude of the LEP. This was accompanied by a significant reduction in the number of withdrawal responses to a given intensity of laser stimulation.…”
Section: Discussionmentioning
confidence: 64%
“…As predicted based on LEP studies in humans 35,36 , peripheral application of capsaicin (causing defunctionalisation of C-fibres 30 ) resulted in a large reduction in the amplitude of the LEP. This was accompanied by a significant reduction in the number of withdrawal responses to a given intensity of laser stimulation.…”
Section: Discussionmentioning
confidence: 64%
“…Notably, the specificity for nociceptive fibers of PCES is still controversially debated [ 34 , 35 ]. The aim of the present study was to further elucidate the understanding of this recently introduced CPM model using PCES as TS with additionally recording of PCES evoked cortical potentials [ 20 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The two most commonly employed methods are those of contact heat evoked potentials (CHEP'S) and laser evoked potentials (LEP's). A recent study has demonstrated excellent sensitivity and specificity for laser evoked potentials with abnormal pinprick sensitivity and reduced IENFD in diabetic neuropathy …”
Section: Small Fibre Functionmentioning
confidence: 99%
“…A recent study has demonstrated excellent sensitivity and specificity for laser evoked potentials with abnormal pinprick sensitivity and reduced IENFD in diabetic neuropathy. 23…”
Section: Evoked Potentialsmentioning
confidence: 99%